KONSEP MASYARAKAT ISLAM MENURUT YUSUF AL-QARDHAWI - Sadan (LPPM STAI Haji Agus Salim, 2024)
Qardhawi has interpreted that the Islamic society is a unique society distinct from all other societies in terms of its constituent elements and specific characteristics. It is a rabbani society (adhering to divine values), humane, and balanced (tawazun). The Islamic society, with its inherent system, can establish religious life and present the social identity of human beings as creatures devoted to God in totality (kaffah). This is a social life directed by faith, purified by acts of worship, guided by a method and ideology that provide salvation, driven by noble aspirations, controlled by ethics (morality), adorned with etiquette (ethics), and regulated by just laws enforced through social leadership or caliphate. This research aims to examine the concept of the Islamic society according to Yusuf al-Qardhawi. The research uses a qualitative research method. It was found that the concept of the Islamic society according to Yusuf al-Qardhawi is a system where the roles and functions are integrated holistically and cannot be separated. Any separation would lead to the dysfunction of the entire system. The Islamic society is a social life guided by systems such as faith, purifying acts of worship, methods and ideologies that provide salvation, noble aspirations that drive the spirit of life, morality that controls, just laws, and social leadership (caliphate). Keywords: Concept of Society, Islam, Yusuf Al-Qardhawi.